Evaluation of geometrical complexity of products based on the analysis of triangulated models - Garashchenko, Yaroslav (Editura "Academica Brâncuşi", Târgu Jiu, 2017)
The results of study evaluation possibilities of geometric complexity of industrial products are presented in this article by analyzing of functional dependence of number of triangular faces on triangulation parameters. As the main parameter of the triangulation was considered maximum size of edges. The dependence study was carried out for basic geometric bodies, which revealed the general regression equation. Test of the regression equation on models of industrial products has confirmed put forward a scientific hypothesis on the evaluation possibility of geometric complexity of industrial products based on the analysis of this functional dependence.
Keywords: additive manufacturing; DFAM; triangulated model; geometric complexity of product